SYNTHESIS, PROPERTIES, AND PHASE RELATIONS OF SOLID SOLUTIONS IN ALKALI METAL TITANOSILICATE SYSTEMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents the synthesis, physicochemical properties, and phase relations of solid solutions in titanosilicate systems containing alkali metal elements. Structural changes, thermal stability, and the interactions between crystalline phases were investigated. Phase characterization was performed using X-ray diffraction (XRD), differential thermal analysis (DTA), and scanning electron microscopy (SEM).